1992
DOI: 10.1111/j.1528-1157.1992.tb02192.x
|View full text |Cite
|
Sign up to set email alerts
|

Placebo‐Controlled Pilot Study of Centromedian Thalamic Stimulation in Treatment of Intractable Seizures

Abstract: Stimulation of centromedian (CM) thalamic nuclei has been proposed as a treatment for seizures. We implanted programmable subcutaneous (s.c.) stimulators into CM bilaterally in 7 patients with intractable epilepsy to test feasibility and safety. Stimulation was on or off in 3-month blocks, with a 3-month washout period in a double-blind, cross-over protocol. Stimuli were delivered as 90-microseconds pulses at 65 pulses/s, 1 min of each 5 min for 2 h/day, with voltage set to half the sensory threshold. Stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
231
3
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(261 citation statements)
references
References 35 publications
6
231
3
7
Order By: Relevance
“…Az 1. táblázat azokat a célpontokat foglalja össze, amelyek antiepilepsziás célzattal stimulációra kerültek [11,12,13,14,15,16,17,18,19,20].…”
Section: Lehetséges Neuromodulációs Célpontok Epilepsziábanunclassified
“…Az 1. táblázat azokat a célpontokat foglalja össze, amelyek antiepilepsziás célzattal stimulációra kerültek [11,12,13,14,15,16,17,18,19,20].…”
Section: Lehetséges Neuromodulációs Célpontok Epilepsziábanunclassified
“…There is currently an ongoing multicenter study in the US, called the SANTE trial (Medtronic, Minneapolis, MN, USA; Clinicaltrials.gov NCT00101933). The stimulation of the centromedian nucleus of the thalamus, at a stimulation frequency ranging from 4 to 185 Hz, has been tested in 78 patients so far [20,[24][25][26]32] where it leads to a significant reduction in seizure frequency of generalised tonic-clonic seizures and of absences, but not of partial complex seizures [23]. Other studies have indicated no reduction in seizure frequency [20,32].…”
Section: Deep Brain Stimulationmentioning
confidence: 99%
“…The potential beneficial effect of electrical stimulation in various encephalopathies with refractory seizures (e.g. Lennox-Gastaut, Dravet, progressive myoclonic epilepsy) is not yet known, despite encouraging results [26,52,53].…”
Section: Optimisation Of Dbs Parametersmentioning
confidence: 99%
“…83 Deep brain stimulation of the CMT may result in hyperpolarization and desynchronization of the ascending reticular and cortical neurons. 83 Fisher et al 23 implanted programmable stimulators into the bilateral CMT in 7 patients with intractable epilepsy (6 with tonic-clonic seizures and 1 with partial complex seizures) to test feasibility and safety. Stimulation was switched on or off in 3-month blocks, with a 3-month washout period in a double-blind, cross-over protocol.…”
Section: Stimulation Of the Cmtmentioning
confidence: 99%
“…Multiple epilepsy centers throughout the world have performed trials over the years using DBS for epilepsy, targeting a variety of CNS structures. 11,12,23,33,78,81 These trials have been based around 2 different strategies: 1) targeting of the CNS structures believed to have a "gating" role in the epileptogenic network, such as the STN or thalamus; 34 and 2) targeting of the ictal onset zone with the theory that stimulation may lead to interference with seizure initiation. The latter strategy might ideally be used in patients with MTL epilepsy given the success in reducing seizures in patients after anterior temporal lobectomy.…”
mentioning
confidence: 99%